Antiviral and Cytotoxic Isocoumarin Derivatives from an Endophytic Fungus Aspergillus oryzae - Zhou, Min; Zhou, Kun; He, Pei; Wang, Kun-Miao; Zhu, Rui-Zhi; Wang, Yue-De; Dong, Wei; Li, Gan-Peng; Yang, Hai-Ying; Ye, Yan-Qing; Du, Gang; Li, Xue-Mei; Hu, Qiu-Fen (Planta Medica, 2016)
Oryzaeins A–D (1-4), four new isocoumarin derivatives, along with five known ones (5-9) were isolated from solid cultures of an endophytic fungus Aspergillus oryzae. Their structures were elucidated by detailed spectroscopic analysis and by comparison with reported data of related derivatives. Among them, compounds 1 and 2 represent the first examples of isocoumarins possessing an unusual 2-oxopropyl group and a rare 3-hydroxypropyl group. Compounds 1 and 2 displayed moderate anti-tobacco mosaic virus activities with inhibition rates of 28.4 % and 30.6 %, respectively, at the concentration of 20 µM. The new compounds showed moderate inhibitory activities against several human tumor cell lines with IC50 values in the range of 2.8–8.8 µM.Supporting information available online at http://www.thieme-connect.de/products
Keywords: Aspergillus oryzae; Trichocomaceae; isocoumarin derivatives; anti-tobacco mosaic virus activity; cytotoxicity